2021
DOI: 10.1155/2021/6663782
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate Exerts Antitumor Effects in Colon Cancer via Regulation of DNMT1 and CDKN2A

Abstract: Peroxisome proliferator-activated receptor alpha (PPARA) is the molecular target of fibrates commonly used to treat dyslipidemia and diabetes. Recently, the potential role of PPARA in other pathological conditions, such as cancers, has been recognized. Here, using bioinformatics analysis, we found that PPARA was expressed at relatively low levels in pancancers, and Kaplan-Meier analyses revealed that high PPARA protein expression was correlated with better survival of patients with colon cancer. In vitro exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 50 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…Shima et al summarized the functions of CDKN2A in colorectal cancers and confirmed that neither CDKN2A promoter methylation nor loss of CDKN2A (p16) was associated with colorectal cancer-specific mortality [ 38 ]. In Kong et al's research [ 39 ], CDKN2A could be a reliable drug target of fenofibrate for colon cancer therapy. As a serine/threonine protein kinase, DAPK1 is considered to be a cancer suppressor gene, which is regulated by calmodulin (CaM) and is a positive regulator of IFN- γ -induced apoptosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shima et al summarized the functions of CDKN2A in colorectal cancers and confirmed that neither CDKN2A promoter methylation nor loss of CDKN2A (p16) was associated with colorectal cancer-specific mortality [ 38 ]. In Kong et al's research [ 39 ], CDKN2A could be a reliable drug target of fenofibrate for colon cancer therapy. As a serine/threonine protein kinase, DAPK1 is considered to be a cancer suppressor gene, which is regulated by calmodulin (CaM) and is a positive regulator of IFN- γ -induced apoptosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…B cell lymphoma cells express extremely low levels of PPARα; therefore, fenofibrate did not increase lipid utilization in the tumors but enhanced the clearance of lipids and blocked hepatic lipid release, leading to reduced tumor growth [ 67 ]. Fenofibrate has also been proposed to suppress colon cancer cell proliferation in vitro and in in vivo xenograft models through epigenetic modifications involving the inhibition of DNA Methyltransferase 1 (DNMT1) [ 68 ]. To summarize, given the highly controversial results regarding the tumor-suppressing or -promoting effects of therapeutic PPARα modulation, especially activation, this intervention seems to be inadequate in the context of cancer.…”
Section: Ppars and Cell Proliferationmentioning
confidence: 99%
“…As another molecular mechanism of PPARα-dependent apoptosis, it has been proposed that PPARα serves as an E3 ubiquitin ligase to induce Bcl2 ubiquitination and degradation, leading to apoptosis [ 179 ]. Additionally in endometrial cancer [ 180 ], breast cancer [ 181 ], glioblastoma [ 182 ], colon cancer [ 68 , 183 ], ovarian cancer [ 56 ], medulloblastoma [ 57 ], neuroblastoma [ 59 ], pancreatic cancer [ 184 ], and NSCLC [ 185 ], the activation of PPARα induced apoptosis. These studies were mainly performed using a cancer cell line in in vitro assays.…”
Section: Ppars and Cell Deathmentioning
confidence: 99%
“…There has been increasing recognition of the crucial role they played in tumor progression. PPARα and PPARγ can affect the development of malignant tumors by regulating survival, metastasis, energy metabolism, immune response, and cell stemness maintenance, which has been reported in various common solid tumors including colon cancer, lung cancer, breast cancer, hepatocellular carcinoma, and so on [ 8 13 ]. PPARδ is widely expressed in the human body but is mainly highly expressed in skeletal muscle and macrophage, which acts as a vital regulatory factor in fatty acid oxidation, keratinocyte differentiation and wound healing [ 14 ].…”
Section: Introductionmentioning
confidence: 99%